The role of information in household energy decisions - Carroll, James (Trinity College (Dublin, Ireland). Department of Economics, 2014)
This dissertation explores the effects of various informational policy interventions in a number of energy markets. Using a number of trials and surveys, this research aims to highlight a household’s underlying energy-reducing motivations, the presence of market failures related to imperfect or asymmetric information and the effect and justification for informational policy intervention. Chapter 1 introduces this dissertation, discusses the specific research questions explored and provides a brief description of the background to energy-related research of this kind (climate change).
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin